Strong Coupling‐Induced Topological Edge‐State Laser in 1D High‐Contrast Grating - Hsu‐Chun Hu; Chia‐Jui Chang; Jhih‐Sheng Wu; Tien‐Chang Lu (Advanced Photonics Research)
In this study, the lattice constant and filling factor of the 1D high‐contrast grating (HCG) to induce strong coupling and weak coupling between transverse guided modes, to create mode parity transitions, are manipulated. In the strong coupling regime, the band inversion happens at the Γ point and changes the topology of the band structure. Hence, this hidden symmetric parameter transforms the HCG structures in the strong coupling and weak coupling regimes to the topological and trivial states, respectively. In the experiment, topological edge‐state lasers by combining topological and trivial lattices are demonstrated. According to bulk‐edge correspondence, a highly localized state unambiguously appears at the structure boundary, which can be utilized as a laser cavity. The laser emission is successfully demonstrated at room temperature in the 1D semiconductor HCG with multiple quantum wells. Compared with the traditional 1D band edge laser, the novel design has a lower threshold and narrower laser linewidth. Compared with the traditional 1D topological edge‐state laser, the innovative design exhibits better robustness against defects. The results pave the way for further novel topological laser cavity designs.